2022
DOI: 10.3389/fpls.2021.820761
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Post-genome-Wide Association Study Analysis for Spike Fertility and Yield Related Traits in Bread Wheat

Abstract: Spike fertility and associated traits are key factors in deciding the grain yield potential of wheat. Genome-wide association study (GWAS) interwoven with advanced post-GWAS analysis such as a genotype-phenotype network (geno-pheno network) for spike fertility, grain yield, and associated traits allow to identify of novel genomic regions and represents attractive targets for future marker-assisted wheat improvement programs. In this study, GWAS was performed on 200 diverse wheat genotypes using Breeders’ 35K A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Cultivars carrying SVs within VRN1 genes showed association with many traits such as lower grain yield, biomass and harvest index compared to those with intact genes. It also has been described before that VRN1 polymorphism is associated with vernalization response, grain yield, spikelet number per spike, spike development, thousand grain weight, stem elongation, heading date, NRI and other developmental traits (Kamran et al, 2013(Kamran et al, , 2014Zheng et al, 2013;Zhang et al, 2014;Voss-Fels et al, 2018;Li et al, 2019;Chumanova et al, 2020;Dreisigacker et al, 2021;Sheoran et al, 2022). Analysis of SV spring alleles together with novel SV alleles revealed correlations with seven traits which have not been evaluated before, e.g., powdery mildew infection, kernels per m 2 , falling number, RUE, NUE, RIE and GCD.…”
Section: Discussionmentioning
confidence: 74%
“…Cultivars carrying SVs within VRN1 genes showed association with many traits such as lower grain yield, biomass and harvest index compared to those with intact genes. It also has been described before that VRN1 polymorphism is associated with vernalization response, grain yield, spikelet number per spike, spike development, thousand grain weight, stem elongation, heading date, NRI and other developmental traits (Kamran et al, 2013(Kamran et al, , 2014Zheng et al, 2013;Zhang et al, 2014;Voss-Fels et al, 2018;Li et al, 2019;Chumanova et al, 2020;Dreisigacker et al, 2021;Sheoran et al, 2022). Analysis of SV spring alleles together with novel SV alleles revealed correlations with seven traits which have not been evaluated before, e.g., powdery mildew infection, kernels per m 2 , falling number, RUE, NUE, RIE and GCD.…”
Section: Discussionmentioning
confidence: 74%
“…To identify unique and novel MTAs for specific traits and under specific conditions, genome-wide association studies have been used extensively in wheat [23,25,[65][66][67][68]. Previous studies have revealed that genes involved in flowering are mostly found on chromosomes 1A, 2B, 3A, 3B, 5A, 6A, 6B, 7A, 7B, and 7D [69][70][71]. In the current study, a total of 30 significant markers associated with five phenological traits were identified.…”
Section: Phenology Variability and Marker Trait Associationmentioning
confidence: 82%
“…However, improving grain yield through the selection process encounters significant challenges primarily due to three factors: (1) the pronounced interaction between genotypes and environmental conditions, (2) relatively low heritability, and (3) the complex genetic architecture of this trait, which depends on several related traits [52]. Thus, selecting for grain yield indirectly via highly heritable and related traits would be a practicable way.…”
Section: The Contribution Of Grain Number To Wheat Yieldmentioning
confidence: 99%